UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN IPAS MATERI WUJUD ZAT KELAS IV UPT SDN 105325 - Mutiara, Rizky; Juwita, Putri; Atika Siregar, Mutia; Amelia, Bunga; Sajidah, Hanna; Apri Husna, Tasya; Kusramadani, Maya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning motivation of fourth-grade students through the use of interactive learning media in the subject of natural sciences (IPAS) on the material of states of matter at UPT SDN 105325. This study uses a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model which is implemented in two cycles. The research subjects were 18 fourth-grade students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used descriptive percentage techniques. The results of the study showed that student learning motivation experienced a significant increase after the implementation of interactive learning media. In the pre-cycle stage, student learning motivation was in the very low category with a percentage of 50%. After the action was carried out in cycle I, student learning motivation increased to 78% with a moderate category. Furthermore, in cycle II student learning motivation increased again to 86% and was in the very high category. Based on these results, it can be concluded that the use of interactive learning media is able to improve student learning motivation in the subject of natural sciences (IPAS) on the material of states of matter. Interactive learning media makes the learning process more interesting, active, and enjoyable, thus encouraging students to be more involved in learning activities.